Study of Chemistry through the digital culture of the anime Dr. Stone: a pedagogical proposal (Research, Society and Development, 2022)
In December 2020 Chinese authorities sent an alert to the World Health Organization (WHO) reporting cases of pneumonia, that from January 2020 had its identity revealed through the new coronavirus that initiated a pandemic in which caused the world to stop, taking over the planet and infecting more than 75 million by 2020. Unfortunately with this panorama there was no alternative but social isolation with remote classes through digital platforms and currently with the introduction of hybrid teaching in Brazil and the World. In this context, the objective of this work is to propose an application for the use and development of educational objects through the anime Dr. Stone, suggested as a teaching instrument addressing contents of the chemistry curriculum component that can be implemented by high school teachers for students of the 1st year classes, working scientific knowledge based on a known universe of these students. The methodology of this pedagogical proposal to be used is the use of Problem Solving as a facilitating element of the teaching and learning processes in which tasks are presented that instill the discussion. The anime stimulates scientific knowledge in line with the content of textbooks. This article can be used as support for teachers who seek to innovate dynamics in the classroom, showing that there are other approaches in Chemistry Teaching, such as working with these Japanese drawings (animes) related to content intended to develop the student's critical sense.